PENYULUHAN BERKREASI DENGAN TAMPILAN WEBSITE YANG MENARIK - Nia Ekawati (ASOSIASI IDEBAHASA KEPRI, 2022)
The development of the industry that is not in line with the provision of adequate manpower, especially for the management and tourism business sectors, has resulted in the need for manpower for these fields to be wide open. Realizing this, in 2006 the local government of the city of Batam took anticipatory steps to build a state vocational school 2 batam with the program of Accounting Expertise, Travel Business, Hospitality Accommodation and Catering located on Jalan Pemuda no. 5 batam center Batam Municipality, Riau Islands Province. SMK Negeri 2 Batam with the motto